Arc controls alcohol cue relapse by a central amygdala mechanism - Pagano, Roberto; Salamian, Ahmad; Zielinski, Janusz; Beroun, Anna; Nalberczak-Skóra, Maria; Skonieczna, Edyta; Cały, Anna; Tay, Nicole; Banaschewski, Tobias; Desrivières, Sylvane; Grigis, Antoine; Garavan, Hugh; et al. (Molecular psychiatry, 2023)
Alcohol use disorder (AUD) is a chronic and fatal disease. The main impediment of the AUD therapy is a high probability of relapse to alcohol abuse even after prolonged abstinence. The molecular mechanisms of cue-induced relapse are not well established, despite the fact that they may offer new targets for the treatment of AUD. Using a comprehensive animal model of AUD, virally-mediated and amygdala-targeted genetic manipulations by CRISPR/Cas9 technology and ex vivo electrophysiology, we identify a mechanism that selectively controls cue-induced alcohol relapse and AUD symptom severity. This mechanism is based on activity-regulated cytoskeleton-associated protein (Arc)/ARG3.1-dependent plasticity of the amygdala synapses. In humans, we identified single nucleotide polymorphisms in the ARC gene and their methylation predicting not only amygdala size, but also frequency of alcohol use, even at the onset of regular consumption. Targeting Arc during alcohol cue exposure may thus be a selective new mechanism for relapse prevention.
Online veröffentlicht: 10. November 2022
Gesehen am 16.07.2024